A Bibliometric Analysis of Food Fraud - Bastian, Ade (Westscience Press, 2023)
Food fraud threatens consumer health, food integrity, and global food supply systems, making it a global issue. Recently, bibliometric analysis has become a useful method for appraising studies in food science and fraud detection. This systematic review employs bibliometric tools to examine food fraud research trends, notable authors, and significant research issues. This investigation searches different scientific databases for relevant 1931–2023 papers. VOSviewer was used to show co-author networks, keyword co-occurrence, pattern quotations, and other bibliometric indicators. The bibliometric study shows a decade-long growth in food fraud studies. This food fraud detection bibliometric study covers the research landscape. These studies help food fraud researchers, policymakers, and other stakeholders discover research trends, prominent authors, significant work, and collaborative networks. These findings can inform future research, information exchange, and evidence-based food safety and consumer protection decisions.